MANFAAT DAN FUNGSI HUTAN MANGROVE BAGI KEHIDUPAN - Riwayati Riwayati (JURNAL KELUARGA SEHAT SEJAHTERA, 2014)
ABSTRACTMangrove trees are plants or plant communities that live in the sea and the land that is affected by tides.  Mangrove habitat is often found at the commeeting spot of the mouth of the river and sea water which then becomes protector of land from ocean waves. From river flow to the mangrove and at high tide, mangrove trees surrounded by salt water or brackish water.  Mangrove forests thrive in the delta region and a broad and large streams with a wide estuary. On the beach there are no rivers , narrow mangrove areas.  Mangrove forests have great tolerance to salinity and can grow in high salinity land where normal plants can not grow . Mangrove forests are the main ecosystems supporting coastal communities . Besides having the ecological function as a provider of food for marine life, coastal erosion anchoring, anchoring the tidal waves and tsunamis, absorbent waste, preventing sea water intrusion, mangrove forests can also serve to provide the food needs of the surrounding population. Kata Kunci : Manfaat Hutan Mangrove, Kehidupan.